PENGARUH DEVIDEN PAYOUT RATIO, RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP PRICE EARNING RATIO PADA SAHAM LQ 45 DI BURSA EFEK INDONESIA - Sabrina, Nina (Jurnal Ilmu Manajemen, 2013)
Formulation of the problem in this study is whether the Dividend Payout Ratio, Return on Assets and Return on Equity together and partially significant effect on Price Earning Ratio at LQ 45 in the Indonesia Stock Exchange. In the study used associative design. The dependent variable used is devident payout ratio, return on assets, and return on equity, while the independent variable is the price earnings ratio. The study population is 83 companies whose shares are included in LQ45 in December 2006- December 2010. The sample was selected is 27 shares of companies that have a certain criteria. The data used is secondary data, with the data collection technique is documentation. The techniques used in the analysis of multiple regression analysis. Based on the obtained results of the testing process 1) Parliament, ROA, ROE together influential significantly toward PER 2) There is a partial effect between Parliament ROA ROE against PER at companies belonging to the group LQ45 respectively 2,360